AMP-activated protein kinase determines apoptotic sensitivity of cancer cells to ginsenoside-Rh2 - Kim, Min-Jung (2013)
Ginseng saponins exert various important pharmacological effects with regard to the control of many diseases, including cancer. In this study, the anticancer effect of ginsenosides on human cancer cells was investigated and compared. Among the tested compounds, ginsenoside-Rh2 displays the highest inhibitory effect on cell viability in HepG2 cells. Ginsenoside-Rh2, a ginseng saponin isolated from the root of Panax ginseng, has been suggested to have potential as an anticancer agent, but the underlying mechanisms remain elusive. In the present study, we have shown that cancer cells have differential sensitivity to ginsenoside-Rh2-induced apoptosis, raising questions regarding the specific mechanisms responsible for the discrepant sensitivity to ginsenoside-Rh2. In this study, we demonstrate that AMP-activated protein kinase (AMPK) is a survival factor under ginsenoside-Rh2 treatment in cancer cells. Cancer cells with acute responsiveness of AMPK display a relative resistance to ginsenoside-Rh2, but cotreatment with AMPK inhibitor resulted in a marked increase of ginsenoside-Rh2-induced apoptosis. We also observed that p38 MAPK (mitogen-activated protein kinase) acts as another survival factor under ginsenoside-Rh2 treatment, but there was no signaling crosstalk between AMPK and p38 MAPK, suggesting that combination with inhibitor of AMPK or p38 MAPK can augment the anticancer potential of ginsenoside Rh2.